Aktivitas Bauran Komunikasi Pemasaran Di Perusahaan Jamu Ibu Tjipto Kota Tegal - Susanto, Agus; Sunardi, Ahmad (Jurnal Komunikator, 2017)
Activities marketing today not just activities selling, but is activity to gain loyal customers. This is not easy work so there needs integrated marketing communications. The example of  integrated marketing communications implementation is by use  marketing communications mix,  which divided in advertising activity, sales promotions, special event &  experiences, public relations & publicity, direct marketing and personal selling.The problems in research discussed by descriptive qualitative approach. This study attempts to give a description of about their activities of marketing communications mix  by Perusahaan Jamu Ibu Tjipto Tegal City  to get drug market share  in  Tega City. Data collection is done by using in-depth interviews with two key participants  and field observation  with compiles literature that supports. Through this research obtained a description of  marketing communications mix activities  in Perusahaan Jamu Ibu Tjipto, which marketing activity not arrayed integrally and adjust human resources and their funds are. The marketing communications mix  not carried out very maximum shown to be just advertising, sales promotions , direct marketing and  personal selling done. Keywords : marketing mix, marketing communication mix, herbal company